Evaluation of a novel score for predicting 2-year outcomes in patients with acute coronary syndrome after percutaneous coronary intervention. Issue 8 (August 2019) - Liu, Yue; Yao, Yi; Tang, Xiao-Fang; Xu, Na; Jiang, Ping; Jiang, Lin; Zhao, Xue-Yan; Chen, Jue; Yang, Yue-Jin; Gao, Run-Lin; Xu, Bo; Yuan, Jin-Qing
Abstract : Background: A novel risk model to predict long-term mortality in patients with acute coronary syndrome (ACS), derived from the EPICOR (long-term follow-up of antithrombotic management patterns in acute coronary syndrome patients) registry, has been released recently and its performance remains to be assessed. The objective is to evaluate the EPICOR score for 2-year mortality risk in ACS patients after percutaneous coronary intervention (PCI). Methods: From January to December in 2013, a total of 6087 consecutive patients presenting with ACS who were scheduled for PCI were enrolled. Use online simplified EPICOR calculator to assess the expected risk of death. Results: Sixty-eight patients (1.1%) died during 2-year follow-up. The areas under the receiver operating characteristics curve for mortality in the overall population, ST-segment elevation myocardial infarction (STEMI), and non-ST-segment elevation ACS were 0.712 (95% CI, 0.650-0.772; p < 0.001), 0.790 (95% CI, 0.676-0.903; p < 0.001), and 0.683 (95% CI, 0.615-0.751; p < 0.001), respectively. Moreover, it was noninferior to the updated Global Registry of Acute Coronary Events (GRACE) risk score. Patients were stratified into three categories: low-risk (n = 3382), medium-risk (n = 2547), and high-risk (n = 158). Kaplan–Meier curve demonstrated significant ongoing divergence in both mortality (0.6% vs 1.3% vs 9.5%; p < 0.001) and major adverse cardiovascular and cerebrovascular events (MACCEs) (11.8% vs 12.3% vs 19.6%; p = 0.014) among them. Multivariate Cox analysis revealed that medium- and high-risk groups predicted 2- and 12-fold hazards of death comparing to the lowest. Yet, it was not a significant predictor for MACCEs after adjusting confounding factors. Conclusion: The simplified EPICOR score showed fair discriminatory power of 2-year mortality in patients with ACS and an improved performance in the STEMI subgroup. It could aid in risk stratification of ACS patients as an independent predictor.